Biofilm-Formation-Related Genes csgD and bcsA Promote the Vertical Transmission of Salmonella Enteritidis in Chicken - Chen, Sujuan; Feng, Zheng; Sun, Hualu; Zhang, Ruonan; Qin, Tao; Peng, Daxin (Frontiers in Veterinary Science, 2021)
The contamination of Salmonella Enteritidis in eggs and chicken meat via vertical transmission has become a worldwide public health concern. Biofilm formation by S. Enteritidis further enhances its antibacterial resistance. However, whether genes related to biofilm formation affect the level of vertical transmission is still unclear. Here, S. Enteritidis mutants ΔcsgD, ΔcsgA, ΔbcsA, and ΔadrA were constructed from wild type strain C50041 (WT), and their biofilm-forming ability was determined by Crystal violet staining assay. Then the median lethal dose (LD50) assay was performed to determine the effects of the selected genes on virulence. The bacterial load in eggs produced by infected laying hens via the intraperitoneal pathway or crop gavage was determined for evaluation of the vertical transmission. Crystal violet staining assay revealed that S. Enteritidis mutants ΔcsgD, ΔcsgA, and ΔbcsA, but not ΔadrA, impaired biofilm formation compared with WT strain. Furthermore, the LD50 in SPF chickens showed that both the ΔcsgD and ΔbcsA mutants were less virulent compared with WT strain. Among the intraperitoneally infected laying hens, the WT strain-infected group had the highest percentage of bacteria-positive eggs (24.7%), followed by the ΔadrA group (16%), ΔcsgA group (9.9%), ΔbcsA group (4.5%), and ΔcsgD group (2.1%). Similarly, among the crop gavage chickens, the WT strain group also had the highest infection percentage in eggs (10.4%), followed by the ΔcsgA group (8.5%), ΔadrA group (7.5%), ΔbcsA group (1.9%), and ΔcsgD group (1.0%). Our results indicate that the genes csgD and bcsA help vertical transmission of S. Enteritidis in chickens.